Enhanced second harmonic generation of MoS2 layers on a thin gold film. Issue 32 (23rd July 2015) - Zeng, Jianhua; Yuan, Maohui; Yuan, Weiguang; Dai, Qiaofeng; Fan, Haihua; Lan, Sheng; Tie, Shaolong
Abstract : The second harmonic generation of MoS2 layers is enhanced significantly by using a thin gold film. Abstract : The linear and nonlinear optical properties of thin MoS2 layers exfoliated on an Au/SiO2 substrate were investigated both numerically and experimentally. It was found that the MoS2 layers with different thicknesses exhibited different colors on the gold film. The reflection spectra of the MoS2 layers with different thicknesses were calculated by using the finite-difference time-domain technique and the corresponding chromaticity coordinates were derived. The electric field enhancement factors at both the fundamental light and the second harmonic were calculated and the enhancement factors for second harmonic generation (SHG) were estimated for the MoS2 layers with different thicknesses. Different from the MoS2 layers on a SiO2 /Si substrate where the maximum SHG was observed in the single-layer MoS2, the maximum SHG was achieved in the 17 nm-thick MoS2 layer on the Au/SiO2 substrate. As compared with the MoS2 layers on the SiO2 /Si substrate, a significant enhancement in SHG was found for the MoS2 layers on the Au/SiO2 substrate due to the strong localization of the electric field. More interestingly, it was demonstrated experimentally that optical data storage can be realized by modifying the SHG intensity of a MoS2 layer through thinning its thickness.